Impulsive Buying Behavior on Online Shopping - M. , Lokesh; V. , Vijayalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Today, the consumer is becoming more prone to impulse buying behavior. It has been recently described as a persuasive, greedily complicated buying behavior in which careful examination of information and alternatives is left out due to the quickness of the decision-making process. To consume can arouse emotional responses and is bound to happen without consideration of the consequences of impulse buying, and it has been identified that it occurs when individuals do not plan, anticipate, or hesitate when making purchasing decisions; that is, when consumers make unintentional, unthoughtful, and prompt purchases. The impulse buying behavior is unintentional, since the consumers are not specifically searching for some products and made no plans to purchase the item. Whenever a decision is to be made, impulsive buying becomes necessary in the corporate world. The degree of dependence on impulsiveness is based on the cost of decisions. If the cost of the decision is high, the dependence on buying is low, and vice versa. The study of the topic is useful to identify and find solutions to the problem and to help make decisions and to find alternative strategies.